Urgensi Pembentukan Undang-Undang Pasar Digital sebagai Instrumen Pengawasan Persaingan Usaha di Era Digital - Rohmat (Jurnal Persaingan Usaha, 2022)
Trading practices are changing as a result of the digital age. Trading operations that were once conducted in a conventional manner have transitioned to an online format. In the wake of the Covid-19 epidemic, there have been an increased number of developments in the digital industry. These actions have an impact on how the Business Competition Supervisory Commission implements business competition oversight (KPPU). Law enforcement against business operators in the digital market has not been made possible by Law Number 5 of 1999 concerning Monopolistic Practices and Unfair Business Competition. The initial goal of this research is to identify and evaluate Indonesia's laws governing unfair competition in the digital market. Second, to examine KPPU's function in monitoring unfair business competition in the digital market. This study used a normative legal approach and a qualitative research design. Law Number 5 of 1999 Concerning the Prohibition of Monopolistic Practices and Unfair Business Rivalry contains the regulations governing unfair business competition in Indonesia. Indonesia has PP Number 80 of 2019 Concerning Trading Through Electronic Systems to Facilitate the Implementation of Trade Through Electronic Systems. Specifically against active foreign business players that have a detrimental impact on Indonesia, the KPPU's role in carrying out enforcement and monitoring in the digital market is less than ideal in practice. The creation of the Digital Market Law is urgently needed in order to implement extraterritorial principles and enhance KPPU's function.